Adoption of e-commerce business Among Small Medium Enterprises (SMES) in Melaka / Khairulanwar Abd Rahman and Muhammad Azri Misti - Abd Rahman, Khairulanwar; Misti, Muhammad Azri (Faculty of Business and Management, 2013)
This study is conducted as a partial fulfilment of the coursework of Industrial Training Project Paper (MKT 669). The title of the study is adoption of e-commerce business among Small Medium Enterprises (SMEs) in Melaka. E-commerce and the use of the internet as a modern day technology to enhance ones business operation have become inevitable in current global business.